Gettysburg : the graphic novel - Butzer, C. M. (Bowen Press/Collins, 2009)
Drawn from first-person letters, speeches, and other primary sources, Butzer presents a comic book style depiction of the Battle of Gettysburg, the national movement to create a memorial at the battle site, and the day of Lincoln's Gettysburg Address in 1863. Lincoln's address itself is played out over sixeen pages, with every phrase given a visual interpretation that will resonate with young readers.